2019
DOI: 10.1186/s13104-019-4533-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and performance of nursing students of Kermanshah-Iran regarding the standards of nosocomial infections control: a cross-sectional study

Abstract: Objectives The aim of this study was to determine the level of knowledge and performance of nursing students in regard to the standards of nosocomial infections control. Results The average score of knowledge and performance of the subjects was 12.49 ± 2.3 from 18 and 43.07 ± 0.67 from 54, respectively. There was a direct and significant correlation between the knowledge and performance of students (r = 0.46, p < 0.0001). There was no statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Our study contributes to the knowledge assessment of Karaganda Medical University students, and also evaluates the adequacy of their training. Our findings agree with some studies on the knowledge of medical students regarding precautionary measures [9,12,18,[25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…Our study contributes to the knowledge assessment of Karaganda Medical University students, and also evaluates the adequacy of their training. Our findings agree with some studies on the knowledge of medical students regarding precautionary measures [9,12,18,[25][26][27][28][29][30][31][32][33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…Among the factors that can influence the occurrence of this infection is the susceptibility of the host, the environment, and the influence of care practices by healthcare professionals [5,6]. The current prevalence rate of HAI in developed countries is around 7% and in developing countries it is around 10% [7,8]. The European Center for Disease Prevention and Control estimates that up to 4.6 million people acquire a HAI each year in acute care settings, which represents the most deadly and costly adverse event in public hospitals across Europe [9].…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, the World Health Organization emphasized the importance of formally including HAI prevention and control modules in healthcare students' undergraduate courses, thereby training them to be active agents of change in clinical practice. Amongst them, nursing students' education and training in this field are essential to ensure the quality and safety of the care provided [8,11]. Nursing students play a critical role in the spread of pathogens and the prevention of infectious diseases as members of the healthcare team, as they treat and care for a wide range of patients throughout their clinical placement [11].…”
Section: Introductionmentioning
confidence: 99%
“…This agreed with Al-Maskari et al (2019) in Oman they find significant correlation between the nurses' knowledge and sexes. However, Majidipour et al (2019) in Iran reported a significant relationship between the nursing studtheir sexes (p= 0.014) and academic educational year (p = 0.015).…”
Section: Methodsmentioning
confidence: 97%